Epigenetic Dynamics in the Function of T-Lineage Regulatory Factor Bcl11b - Sidwell, Tom; Rothenberg, Ellen V. (Frontiers in Immunology, 2021)
The transcription factor Bcl11b is critically required to support the development of diverse cell types, including T lymphocytes, type 2 innate lymphoid cells, neurons, craniofacial mesenchyme and keratinocytes. Although in T cell development its onset of expression is tightly linked to T-lymphoid lineage commitment, the Bcl11b protein in fact regulates substantially different sets of genes in different lymphocyte populations, playing strongly context-dependent roles. Somewhat unusually for lineage-defining transcription factors with site-specific DNA binding activity, much of the reported chromatin binding of Bcl11b appears to be indirect, or guided in large part by interactions with other transcription factors. We describe evidence suggesting that a further way in which Bcl11b exerts such distinct stage-dependent functions is by nucleating changes in regional suites of epigenetic modifications through recruitment of multiple families of chromatin-modifying enzyme complexes. Herein we explore what is - and what remains to be - understood of the roles of Bcl11b, its cofactors, and how it modifies the epigenetic state of the cell to enforce its diverse set of context-specific transcriptional and developmental programs.